2010
DOI: 10.1097/paf.0b013e3181c6bec2
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Caused by Fibrovascular Esophageal Polyp

Abstract: Benign tumors of the esophagus are rare but can lead be fatal when aspirated into the upper airway. Here, we describe a sudden death due to aspiration of a fibrovascular polyp supported by a review of 11 cases from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…5,6 Recently, a case of sudden death owing to aspiration of a GVFP has been reported, bringing the total number of reported deaths since 1854 from this lesion to 12. 7 Clinical diagnosis is challenging, and polyps may be missed with endoscopic and radiologic examination. This is in part due to the normal appearing mucosal surface, which gives the appearance as part of the normal esophageal wall.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recently, a case of sudden death owing to aspiration of a GVFP has been reported, bringing the total number of reported deaths since 1854 from this lesion to 12. 7 Clinical diagnosis is challenging, and polyps may be missed with endoscopic and radiologic examination. This is in part due to the normal appearing mucosal surface, which gives the appearance as part of the normal esophageal wall.…”
Section: Discussionmentioning
confidence: 99%
“…These early symptoms are nonspecific and might lead to misdiagnosis. According to the Ramalho et al's report [4], showed that the average age for FVP to occur is 57.5 years. Where 64% of patients had dysphagia, 31% of patients had respiratory symptoms and 41% of patients suffered from esophagus reflux [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Ramalho et al's report [4], showed that the average age for FVP to occur is 57.5 years. Where 64% of patients had dysphagia, 31% of patients had respiratory symptoms and 41% of patients suffered from esophagus reflux [3,4]. Furthermore, many papers reported that FVP is one of the causes of sudden onset of suffocation [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several endoscopic resections have been reported, with only three cases requiring a conversion to an open approach. Concerns have been raised regarding potential for massive haemorrhage using the endoscopic approach, but such complications have not been reported. LASER resection has been described.…”
mentioning
confidence: 99%